2018
DOI: 10.1371/journal.pone.0207062
|View full text |Cite
|
Sign up to set email alerts
|

Annotation and analysis of the mitochondrial genome of Coniothyrium glycines, causal agent of red leaf blotch of soybean, reveals an abundance of homing endonucleases

Abstract: Coniothyrium glycines, the causal agent of soybean red leaf blotch, is a USDA APHIS-listed Plant Pathogen Select Agent and potential threat to US agriculture. Sequencing of the C. glycines mt genome revealed a circular 98,533-bp molecule with a mean GC content of 29.01%. It contains twelve of the mitochondrial genes typically involved in oxidative phosphorylation (atp6, cob, cox1-3, nad1-6, and nad4L), one for a ribosomal protein (rps3), four for hypothetical proteins, one for each of the small and large subun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 51 publications
(55 reference statements)
2
12
0
Order By: Relevance
“…Linear versions have also been observed and some circular version could actually exist as linear concatemers generated by a rolling circle type DNA replication mechanism ( Bendich, 1993 ; Hausner, 2003 , 2012 ; Bullerwell and Lang, 2005 ; Baidyaroy et al, 2011 ; Valach et al, 2011 ; Chen and Clark-Walker, 2018 ). Mitochondrial genome architecture and size are highly variable among the fungi due to recombination events promoted by repeats and by the presence and activities of mobile elements such group I and group II introns and intron-encoded proteins (IEPs) ( Aguileta et al, 2014 ; Wu and Hao, 2014 , 2019 ; Franco et al, 2017 ; Repar and Warnecke, 2017 ; Deng et al, 2018 ; Stone et al, 2018 ; Zubaer et al, 2018 ; Kolesnikova et al, 2019 ; Kulik et al, 2020 ; Liu et al, 2020b ). Like other fungi, most of the mitogenome variation observed among the examined members of the Ophiostomatales is due to the absence and presence of introns.…”
Section: Discussionmentioning
confidence: 99%
“…Linear versions have also been observed and some circular version could actually exist as linear concatemers generated by a rolling circle type DNA replication mechanism ( Bendich, 1993 ; Hausner, 2003 , 2012 ; Bullerwell and Lang, 2005 ; Baidyaroy et al, 2011 ; Valach et al, 2011 ; Chen and Clark-Walker, 2018 ). Mitochondrial genome architecture and size are highly variable among the fungi due to recombination events promoted by repeats and by the presence and activities of mobile elements such group I and group II introns and intron-encoded proteins (IEPs) ( Aguileta et al, 2014 ; Wu and Hao, 2014 , 2019 ; Franco et al, 2017 ; Repar and Warnecke, 2017 ; Deng et al, 2018 ; Stone et al, 2018 ; Zubaer et al, 2018 ; Kolesnikova et al, 2019 ; Kulik et al, 2020 ; Liu et al, 2020b ). Like other fungi, most of the mitogenome variation observed among the examined members of the Ophiostomatales is due to the absence and presence of introns.…”
Section: Discussionmentioning
confidence: 99%
“…The mt-genome of another member of the Pleosporales, Coniothyrium glycines, the causal agent of soybean red leaf blotch, contains 12 mt-genes and 32 introns with a high number of homing endonucleases that represent approximately 54.1% of the mt-genome. However, the gene order of nad6-rnl-atp6, is conserved among members of Pleosporales (Stone et al, 2018). Kolesnikova et al (2019) analyzed species of the genus Armillaria (Agaricales) and found that the mt-genome varied in size (98,896-122,167 bp) and arrangement.…”
Section: Conservation Vs Plasticitymentioning
confidence: 99%
“…Blast searches of the corresponding sequences, however, provided evidence for homology with a GIY‐YIG HE (Table ) and a LAGLIDADG HE, respectively (Table ). Like many other species of fungi (Jalalzadeh et al., 2015; Pogoda et al., 2019; Stone et al., 2018), plants (Cho, Qiu, Kuhlman, & Palmer, 1998), and even animals (Fukami, Chen, Chiou, & Knowlton, 2007; Schuster et al., 2017), the cox1 gene seems to be a hotspot of HEG‐encoding introns in smut fungi.…”
Section: Resultsmentioning
confidence: 98%